Sexual dimorphism and morphological integration in the orchid bee brain - Denise Yamhure-Ramírez; Peter C. Wainwright; Santiago R. Ramírez (Scientific Reports)
Abstract Sex-specific behaviours are common across animals and often associated with sexual dimorphism in the nervous system. Using micro-CT scanning we standardized sex-specific brain atlases and tested for sexual dimorphism in the brain of the orchid bee Euglossa dilemma, a species with marked sex differences in social behaviour, mating strategies and foraging. Males show greater investment in all primary visual processing neuropils and are uniquely integrated with the central complex, evidenced by a strong positive covariation. This suggests that males invest more on locomotor control, flight stability and sky-compass navigation which may have evolved in response to sex-specific behaviours, like courtship display. In contrast, females have larger mushroom bodies that strongly and positively covary with the optic lobes and have increased volume of the Kenyon cell cluster, implying greater capabilities for visual associative memory. We speculate this is an adaptation to social and nest-building behaviours, and reliance on learning visual landmarks required for central place foraging. Our study provides the first record of sexually dimorphic morphological integration in the brain of an insect, an approach that revealed sex-specific brain traits that lack an apparent morphological signal. These subtle differences provide further evidence for the causal link between brain architecture and behaviour.